O teclado eletrônico como instrumento orquestral: análise e demonstração da peça Sir Lancelot and the black knight de Rick Wakeman - Lincoln Meireles Ribeiro dos Santos (2008)
Orchestral experimentations using electronic keyboards and their resources have been the focus of my work for more than 20 years. The objective of this study is to evaluate the functionality of orchestral experimentations through the analysis, arrangement and demonstration of the piece Sir Lancelot and The Black Knight, written by Rick Wakeman, an English musician. The theoretical aspect of the research was developed through literature review, regarding the evolution of the electronic keyboards, the social, political and cultural environment from the 50s to the 80s when appeared the Rock Progressive and the historical basis about the legend that inspired the studied piece. The analysis had been guided by the Modelo Tripartite of Jean Molino according to Jean-Jacques Nattiez and, mainly for the Sistema de Análise de Arte Comparada (SAAC) of Sandra Loureiro de Freitas Reis.This study intends to make possible the use of the electronic keyboards as an orchestral laboratory, demonstrating the use of the electronic resources associated to the knowledge acquired in the Academy.